Fighting for Funding and against Inequality Post-COVID-19 - de Wit, Hans; Altbach, Philip G. (International Higher Education, 2021)
The COVID-19 pandemic has opened a Pandora’s box about the future role of higher education. Online education was acceptable for a short period, but made clear that institutions of higher education are also a living community of faculty and students. The pandemic has put a spotlight on the importance of international research collaboration. But because of severe economic downturns, the pandemic has dramatically worsened inequalities within the higher education and research sector.